Hubungan Antara Pengetahuan Dengan Persepsi Ibu Hamil Tentang Vaksin Covid-19 - Inda Permata Sari; Yuniarti Mbuik; Euvanggelia Dwilda Ferdinandus (Jurnal Sehat Mandiri, 2022)
Pregnancy with Covid-19 increases the risk of maternal morbidity. Covid-19 vaccination in pregnant women as an effort to reduce the transmission of Covid-19 in pregnancy. The low Covid-19 vaccination achievement of 38 out of 1,150 pregnant women coverage can be influenced by the perception of pregnant women. This study aims to determine the relationship between the level of knowledge and perceptions of pregnant women about the Covid-19 vaccine. Cross sectional design, purposive sampling technique with 169 pregnant women as respondents. Univariate data analysis in frequency distribution and bivariate analysis of chi-square test. The results showed the characteristics of pregnant women Respondents were 134 pregnant women (79.3%) aged 20-35 years, 52 pregnant women (30.8%) with less knowledge about the Covid-19 vaccine and 65 pregnant women (38.5%). ) has a negative perception. The test results obtained p-value = 0.000 (p <0.05), there is a relationship between the level of knowledge and the perception of pregnant women about the Covid-19 vaccine. The level of knowledge of pregnant women is sufficient and the perception is positive at the Plaju Palembang Health Center, but there are still some who have a negative perception. It is recommended to increase the knowledge of pregnant women with education about the Covid-19 vaccine in pregnancy through pregnant women involving their husbands and families to vaccinate Covid-19 without hesitation.